Pengaruh Label Halal, Kesadaran Harga, dan Bauran Pemasaran terhadap Keputusan Pembelian Produk Kosmetik di Livi Beauty House - Sauri, Supian; Radhiati, Raisa; Ghani, Abdul; Halimah, Halimah; Irgianoor, Muhammad (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to evaluate the influence of independent variables, specifically halal labeling (X1), price awareness (X2), and marketing mix (X3), on the purchasing decisions (Y) regarding cosmetic products at Livi Beautyhouse. This research was conducted to address inconsistencies found in previous studies. It adopts a quantitative approach in the form of a field study. Data were collected through the distribution and retrieval of questionnaires. The sampling method employed was purposive sampling, involving 96 student respondents. Data analysis was performed using multiple linear regression with the assistance of SPSS version 23 software. The results revealed that each variable, halal labeling (X1), price awareness (X2), and marketing mix (X3) has a substantial impact on purchasing decisions (Y). Simultaneously, the independent variables of halal labeling (X1), price awareness (X2), and marketing mix (X3) collectively exert a significant influence on purchasing decisions (Y) with a significant value of 0.000 0.05 and an of (60.184) (2.466).